Genetics analysis & principles - Brooker, Robert J. (McGraw-Hill Education, 2015)
Takes an experimental approach to understanding genetics. By weaving one or two experiments into the narrative of each chapter, this title helps students explore the scientific method and understand the genetic principles that have been learned from these experiments.